2008
DOI: 10.1371/journal.ppat.1000072
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Compatibility and Virulence of Reassortants Derived from Contemporary Avian H5N1 and Human H3N2 Influenza A Viruses

Abstract: The segmented structure of the influenza virus genome plays a pivotal role in its adaptation to new hosts and the emergence of pandemics. Despite concerns about the pandemic threat posed by highly pathogenic avian influenza H5N1 viruses, little is known about the biological properties of H5N1 viruses that may emerge following reassortment with contemporary human influenza viruses. In this study, we used reverse genetics to generate the 63 possible virus reassortants derived from H5N1 and H3N2 viruses, containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
131
3
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(141 citation statements)
references
References 44 publications
6
131
3
1
Order By: Relevance
“…Strikingly, three viruses exhibited substantial lethality for mice with MLD 50 s of ≤10 pfu. Our data suggest that of the eight segments in the human virus, Tok07 PB2 is indispensible for the conversion of reassortant H5 viruses into the highly pathogenic phenotype and that, in contrast to the findings of Chen et al (9), viruses with substantial virulence indeed can be generated by reassortment of avian H5N1 and human H3N2 viruses. Our study thus provides valuable information for preparedness for future pandemics that could be caused by reassortants between avian H5N1 and human influenza viruses, including the recently emerged pandemic H1N1 virus.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…Strikingly, three viruses exhibited substantial lethality for mice with MLD 50 s of ≤10 pfu. Our data suggest that of the eight segments in the human virus, Tok07 PB2 is indispensible for the conversion of reassortant H5 viruses into the highly pathogenic phenotype and that, in contrast to the findings of Chen et al (9), viruses with substantial virulence indeed can be generated by reassortment of avian H5N1 and human H3N2 viruses. Our study thus provides valuable information for preparedness for future pandemics that could be caused by reassortants between avian H5N1 and human influenza viruses, including the recently emerged pandemic H1N1 virus.…”
Section: Discussioncontrasting
confidence: 83%
“…It therefore is important to evaluate the pathogenicity of such reassortants. Chen et al (9) attempted to generate 63 (2 6 − 1 parent virus) reassortant viruses between A/Thailand/16/04 (H5N1) and A/Wyoming/3/03 (H3N2) viruses containing the H5N1 HA and NA genes, together with an additional virus that had H5 HA and N2 NA genes and tested the virulence in mice of 39 of the reassortant viruses generated. They found that these reassortant viruses displayed a broad spectrum of pathogenicity in the mouse model.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The wholesale acquisition of polymerase genes encoding PB1 has been observed in two prior pandemic outbreaks; viruses responsible for the ''Asian'' influenza pandemic in 1957 and the ''Hong Kong'' influenza pandemic in 1968 were reassortants that contained a PB1 subunit of avian origin with the remainder of the polymerase derived from a human virus (29). Experimental analysis has shown that in certain cases, reassorted human influenza polymerases containing an avian PB1 have enhanced activity (30) or support a more pathogenic infection (31), although the potential contribution of PB1-F2 cannot be excluded (32). The current 2009 A(H1N1) pandemic virus is a reassortant as well, containing a replication complex composed of avian-origin PB2 and PA, human-origin PB1, and classic swine-origin NP (21,28).…”
Section: Discussionmentioning
confidence: 99%
“…In the last years great efforts have been undertaken to reveal the mechanisms of influenza-host cell interactions. Studies focused either on pathogenesis in humans [11], discovery of novel drug targets, antiviral therapies and biomarker research [1], or on analysis of virulence and adaptation strategies of avian influenza virus [5]. Among the Influenza viruses, influenza A has been shown to interact with host cell proteins throughout the virus life cycle [34].…”
Section: Introductionmentioning
confidence: 99%